Attitudes toward psychedelic therapy among medical and nursing students: A cross-sectional survey study - Diego Castellano-Ramírez; Elisa Hernández-Álvarez; Lucas F. Borkel; Jaime Rojas-Hernández; Domingo Quintana-Hernández; Luis Alberto Henríquez-Hernández (PLoS ONE, 2026)
Psychedelic-assisted therapy is regaining attention as a promising approach to treating mental health disorders. This research aimed to compare related factors regarding the therapeutic use of psychedelics between medical and nursing students, addressing a notable gap in existing research. A cross-sectional survey was conducted at the University of Las Palmas de Gran Canaria (Spain) during the 2024/2025 academic year, including 325 students—204 from nursing and 121 from medicine—who completed a 7-item Likert-scale questionnaire assessing attitudes, perceived knowledge, and beliefs about the therapeutic potential, risks, and regulation of psychedelics, alongside sociodemographic data. Results revealed a growing interest in the therapeutic potential of psychedelics, although concerns persist. Gender and age were significantly associated with beliefs, with women reporting lower levels of perceived knowledge about psychedelics and older students exhibiting greater openness toward their therapeutic potential. Medical students demonstrated higher levels of perceived knowledge and greater agreement with therapeutic applications compared to nursing students, who more strongly associated psychedelic use with psychiatric risk. Participants with prior psychedelic use were more supportive of legalization and therapeutic use, highlighting the impact of personal experience. Formal education on psychedelics was linked to more favourable attitudes and increased knowledge, suggesting that training may reduce stigma and support evidence-based policy. Overall, students showed a cautiously optimistic view toward psychedelic therapies. These findings underscore the importance of integrating content on emerging treatments into health sciences curricula to foster informed, critical perspectives among future clinicians.